Justiça distributiva e equidade no transporte: Legado dos megaeventos e desigualdades de acesso a oportunidades no Rio de Janeiro - Rafael H. M. Pereira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– Public transport policies play a key role in shaping the ease with each people from different social groups and income levels can access job opportunities, health services and education. Thus, these policies have important implications for the promotion of more just and inclusive cities. This research contributes in three different ways to the literatures on transport accessibility, equity and impact assessment of transport policies. First, the research proposes a theoretical framework for assessing accessibility impacts of transport policies from a distributive justice perspective. Second, it demonstrates the means by which the proposed theoretical framework can be applied to a city in a developing country. This framework is applied to evaluate the transportation policies developed in Rio de Janeiro in preparation for hosting the 2014 World Cup and the 2016 Olympic Games. This research examines how the transport legacy of those megaevents impacted accessibility to job opportunities, health and education services for the population of different income levels. The study presents -post and counterfactual analyses of the policies implemented between 2014 and 2017 and ex-ante analysis of an as yet unfinished BRT project. The results show that the expansion in transport infrastructure between 2014 and 2017 could have generated accessibility gains, but these gains were generally offset by the reduction in bus service levels that followed an economic crisis that hit the city after the Olympics Even if the city had not been hit by the economic crisis, transport policies in that period would have had regressive impacts. Those policies have generated higher accessibility gains for wealthier groups, increasing inequalities in access to opportunities. The evaluation of the future accessibility impacts of the unfinished BRT corridor, nonetheless, indicates that such project could significantly improve access to job opportunities for a large share of Rio's population, particularly lower-income groups. Finally, this research shows how the equity and impact assessment of transport projects based on cumulative opportunity accessibility - the most common practice adopted by academic studies and transportation agencies - are sensitive to spatial scale and zoning scheme of analysis as well as on the time threshold considered in the accessibility indicator.
Keywords: H51; I18; 330; accessibility; equity; distributive justice; equality of opportunity; Rio de Janeiro; legacy; megaevents; Olympic Games; transport policies; BRT; public transport; urban mobility